Possibilities in an Environment of Perceived Impossibility: Exploring Imagination and Conflict Transformation in Cyprus - Johansson,Ellen (2023)
When conflict is protracted, there can be a perception of impossibility regarding change of the situation towards peace or transformation as the conflict has defied this and persisted despite time and efforts. This study aims to investigate if and how imagination can be used in conflict transformation, despite this perceived impossibility, by applying a qualitative method and conducting a textual analysis of how imagination has been used strategically in Cyprus to address the Cyprus problem through the Cyprus Futures project. The study shows that many important ways that imagination can be used for conflict transformation has been present in the Cyprus Futures project and can help meet some of the challenges in transforming protracted conflicts. However, within some of the ways imagination can be used, true transcendence of existing patterns and perceptions is not yet reached through this practice which may be necessary to break out of destructive conflict cycles and make the impossible possible.
Keywords: Imagination; Conflict transformation; protracted conflict; Cyprus problem